Impaired vasomotor function induced by the combination of hypertension and hypercholesterolemia - YILDIRIM, ALPER; KURTEL, HIZIR (ELSEVIER SCIENCE INC, 2013)
Although it is well known that endothelial function is compromised in the presence of either hypertension (HTN) or hypercholesterolemia (HCh), less is known about whether and how the combination of these risk factors (HTN+HCh) results in impaired endothelium-dependent dilation (EDD). The aims of this study were to evaluate the influence of HTN+HCh on vasomotor function and to identify the mechanisms that underlie the altered vascular reactivity elicited by HTN+HCh. Endothelium-dependent and -independent vasomotor responses of aortic vessels were studied in mice with diet-induced HCh and/or HTN induced by chronic administration of either angiotensin II (AngII) or deoxycorticosterone acetate-salt. HTN+HCh elicited an impairment of EDD that appeared between each risk factor alone. Incubation with catalase resulted in more severe EDD impairment. Each risk factor enhanced vascular H2O2 production, but a larger response was noted with HTN+HCh. An attenuated EDD was not observed in AngII type la receptor deficient (AT1r(-/-)) mice, but AT1r(-/-) bone marrow chimeras exhibited more profound impairment compared with wild-type. HTN+HCh does not exert an additive effect of vasomotor dysfunction compared with either risk factor alone, and both H2O2 and blood cell-associated AT1r contribute to the impaired EDD responses in mice with HTN+HCh. J Am Soc Hypertens 2013;7(1):14-23. (C) 2013 American Society of Hypertension. All rights reserved.
Keywords: Angiotensin II type-1 receptors; endothelium-dependent vasodilation; hydrogen peroxide; risk factors; NITRIC-OXIDE SYNTHASE; ENDOTHELIUM-DEPENDENT CONTRACTIONS; CARDIOVASCULAR RISK-FACTORS; II-INDUCED HYPERTENSION; ANGIOTENSIN-II; HYDROGEN-PEROXIDE; T-CELL; MICROVASCULAR RESPONSES; OXIDATIVE STRESS; NADPH OXIDASE